Mechanics of nanocomposites homogenization and analysis - Dabbagh, Ali (Mechanical engineering); Ebrahimi, Farzad, 1979- (Boca Raton, FL : CRC Press, 2020)
Emphasizing the static and dynamic behaviors of nanocomposite single- or multilayered structures in the framework of continuum mechanics-based approaches, Mechanics of Nanocomposites: Homogenization and Analysis investigates mechanical behaviors of polymeric matrices strengthened via various nanofillers and nanoparticles such as carbon nanotubes (CNTs), graphene platelets (GPLs), and graphene oxides (GOs). It covers equivalent properties of nanocomposites that are obtained via homogenization techniques based on micromechanics approaches. In addition, this comprehensive book: Discusses the effects of various nanofillers and identifies the amount of the improvement that can be induced in the stiffness of the polymeric nanocomposites by adding a finite content of the aforementioned nanosize reinforcements Magnifies the effect of the number of the stacking plies of the multi-layered nanocomposite structures on both static and dynamic responses of the continuous systems manufactured from such sandwich structures Presents a wide range of analytical and numerical solution procedures Investigates the effects of porosity along with mechanical characteristics of nanocomposites Considers the time-dependency of the material properties of the viscoelastic polymeric nanocomposite structures Performs analyses using an energy-based approach incorporated with the strain-displacement relations of both classical and higher-order shear deformable beam, plate, or shell theorems Aimed at researchers, academics, and professionals working across mechanical, materials, and other areas of engineering, this work ensures that readers are equipped to fully understand the mechanical characteristics of nanocomposite structures so that they can design, develop, and apply these materials effectively.
OCLC-licensed vendor bibliographic record.
Keywords: Nanocomposites (Materials) -- Mechanical properties; TECHNOLOGY / Engineering / Mechanical